Qualitative Composition of People Suffering from Cancer in Babil Governorate - Shamkhi, Samah Ibrahim; Hashem, Zainab Rahim (Journal of Ecohumanism, 2024)
The research aims to study the qualitative composition of people suffering from cancerous diseases in the study area, relying on a set of digital data issued by hospitals and health institutions related to the disease. The researcher proceeded to classify the disease phenomenon and analyze it quantitatively for the period (2017-2022). The study period was classified into three The first was extended for two years before the spread of the Corona epidemic and two years after the epidemic. We relied on data from the Iraqi Ministry of Health and its affiliated institutions from hospitals and health care centers in Babil Governorate, where the most common types (14 types) of cancer diseases that were available in the study area were studied..